Electrochemical Study of the Corrosion Inhibition of Mild Steel in Hydrochloric Acid by Amlodipine Drug - Akpan, I. A; Offiong, N. O (International Journal of Chemistry and Materials Research, 2014)
The inhibition of mild steel corrosion in acidic medium inhibited by amlodipine at room temperature (30oC) was monitored via the linear polarization resistance electrochemical technique using a variable voltage, DC power supply (AC mV metre, 2channel model GVT 427). The concentration of the acid medium was maintained at 0.1M HCl throughout the experiment. The inhibition efficiency was found to increase with increase in the concentration of the drug in the corrosive medium. The highest polarization resistance (Rp) (1083Ωcm2) was obtained at the highest inhibitor concentration (10.0×10-3M) while the lowest Rp (567Ωcm2) was recorded against the lowest inhibitor concentration (2.5×10-3M). The adsorption mode of the drug was found to be by monolayer chemisorptions having found the experimental data obeyed the Langmuir adsorption isotherm.